2016
DOI: 10.1093/jb/mvw026
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of structural elements in a class-I cyclic di-GMP riboswitch to elucidate its regulatory mechanism

Abstract: The Vc2 riboswitch possesses an aptamer domain belonging to the class-I c-di-GMP riboswitch family. This domain has been analysed and the molecular mechanism by which it recognizes the c-di-GMP ligand has been elucidated. On the other hand, the regulatory mechanism of the full-length Vc2 riboswitch to control its downstream open reading frame (ORF) remains largely unknown. In this study, we performed in vivo reporter assays and in vitro biochemical analyses of the full-length riboswitch and its aptamer domain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 34 publications
3
32
0
Order By: Relevance
“…The neighboring A91 was also fixed inside the riboswitch core upon c‐di‐GMP recognition (Kulshina et al., ; Smith et al., ). Ligand‐dependent enhancement of the protection was also observed at the P2‐GAAA loop and P3‐R(Vc2) motif, which also suggested that binding of c‐di‐GMP stabilizes the folded structure of the riboswitch, in which the P2‐GAAA loop is docked stably to the P3‐R(vc2) motif through tetraloop–receptor interaction (Inuzuka et al., ). Changes in the protection patterns at the aptamer domain strongly suggest that the recognition of c‐di‐GMP induces the ligand‐bound structure showed by X‐ray crystallographic studies.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The neighboring A91 was also fixed inside the riboswitch core upon c‐di‐GMP recognition (Kulshina et al., ; Smith et al., ). Ligand‐dependent enhancement of the protection was also observed at the P2‐GAAA loop and P3‐R(Vc2) motif, which also suggested that binding of c‐di‐GMP stabilizes the folded structure of the riboswitch, in which the P2‐GAAA loop is docked stably to the P3‐R(vc2) motif through tetraloop–receptor interaction (Inuzuka et al., ). Changes in the protection patterns at the aptamer domain strongly suggest that the recognition of c‐di‐GMP induces the ligand‐bound structure showed by X‐ray crystallographic studies.…”
Section: Resultsmentioning
confidence: 94%
“…The main objective of this study was to experimentally elucidate the ligand‐bound and ligand‐free structures of the riboswitch. However, a previous study involving chemical probing of the full‐length riboswitch RNA with dimethyl sulfate (DMS) showed no significant changes in modification pattern with/without c‐di‐GMP (Inuzuka et al., ). These results were due to the intrinsic flexibility of the riboswitch structures and also to the experimental conditions that may not have been optimized for DMS modifications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study on V. cholerae , we showed that lowered c‐di‐GMP levels led to the production of TfoY under standard laboratory conditions (e.g. in LB medium) and we and others suggested that this c‐di‐GMP‐dependent control occurred at the translational level (Inuzuka et al ., ; Metzger et al ., ). Interestingly, Gode‐Potratz et al .…”
Section: Resultsmentioning
confidence: 97%